GENESIS, a knowledge-based genetic engineering simulation system for representation of genetic data and experiment planning. - Friedland, P (1982)
We have built a knowledge-based genetic engineering simulation system-- GENESIS-- capable of representing both domain-specific and general knowledge. Information is stored within a hierarchically-organized framework composed of structures called units. A series of sophisticated editors enables no-computer specialist molecular geneticists to construct a knowledge base through direct interaction with the computer. Three types of knowledge specific to the domain of molecular genetics, MAPS, sequences and RULES are discussed in detail with examples.